State of the art on Advanced Nursing Practice: reflections for the agenda in Brazil - Livia Angeli-Silva; Tatiana de Sena Leitão; Helena Maria Scherlowski Leal David; Nildo Batista Mascarenhas; Sônia Acioli; Tiago Parada Costa Silva (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to review the state of the art on Advanced Nursing Practices. Methods: a scoping review of existing publications up to 2020, in the PubMed/MEDLINE, SciELO, LILACS, BDENF, Web of Science and Scopus databases, identified by descriptors "Prática Avançada de Enfermagem" or "Advanced Practice Nursing". A total of 184 documents were selected. The characterization of this study was carried out, followed by the construction of an overview of different regions of the world. Results: studies showed an increasing trend in the last decade, being present in all continents, although 43.5% correspond to opinion articles, comments, editorials and event reports. Even with similar aspects, the justifications for Advanced Nursing Practices reflect specific regional needs. Final Considerations: the studies still lack methodological variety and emphasis on the specificities of countries and their health systems, in addition to greater detail on labor regulation, professional training and the impacts of these practices in nursing.